The Academic Development approach to academic literacy in higher education South Africa: a disconnect between teaching and assessment. - Sebolai, Kabelo (Journal for Language Teaching, 2022)
Academic literacy, the ability to cope with the discourse demands of higher education, is believed to be a factor in the poor graduation rates among South African students. As a result, interventions to deal with low levels of this ability have been part of the broader effort by universities to boost student completion rates. In South Africa, two approaches to these interventions and the theories informing them have seen the light of day to date. In the main, these approaches and their theories have either been generic or discipline-specific in orientation, with the latter being currently the most embraced of the two. The present article is a case study of these two theorizations of academic literacy and aims to demonstrate that although the discipline-specific approach is the most favoured, a void exists currently regarding how its teaching might translate into assessment. This is the case especially when viewed from the way that this approach has been pursued in the field of Academic Development in post-apartheid South Africa. The article demonstrates, in other words, that while the discipline-specific approach, as pursued by the field of Academic Development, is convincing in terms of how it advocates for teaching, nothing equivalent has come from this field to balance the approach from the side of assessment.